(untitled) (Research, Society and Development, 2020)
Describe the effectiveness of chemotherapy in palliative care in cancer patients. This is an integrative review study started in April 2020, using Google Scholar, Medline, Scielo and PubMed as database. The PICO strategy was used to construct the research topics. According to this search method, 255 articles were reached, and the definition by determining the exclusion criteria was selected 27 original articles used in this review. The selected articles were analyzed and organized into four thematic categories, namely: Palliative Care in Oncology Patient, Palliative Chemotherapy in Solid Tumors, Palliative Chemotherapy versus Quality of Life and Skills and Nursing Care in Palliative Chemotherapy. An acceptance of palliative chemotherapy is noted. in some cases and in others more risks than benefits are identified, making the choice of this treatment improper. The choice of treatment must be made following individualized assessments carried out by the responsible team aiming at the best quality and life expectancy of each patient.